Early damage enhances compensatory responses to herbivory in wild lima bean - Bustos-Segura, Carlos; González-Salas, Raúl; Benrey, Betty (Frontiers in Plant Science, 2022)
Damage by herbivores can induce various defensive responses. Induced resistance comprises traits that can reduced the damage, while compensatory responses reduce the negative effects of damage on plant fitness. Timing of damage may be essential in determining the patterns of induced defenses. Here, we tested how timing and frequency of leaf damage affect compensatory responses in wild lima bean plants in terms of growth and seed output, as well as their effects on induced resistance to seed beetles. To this end, we applied mechanical damage to plants at different ontogenetical stages, at one time point (juvenile stage only) or two time points (seedling and juvenile stage or juvenile and reproductive stage) . We found that plants damaged at the seedling/juvenile stage showed higher compensatory growth, and seed output compared to plants damaged only at the juvenile stage or juvenile/reproductive stage. Seeds from plants damaged at the juvenile and juvenile/reproductive stages had fewer beetles than seeds from undamaged plants, however this was driven by a density dependent effect of seed abundance rather than a direct effect of damage treatments. We did not find differences in parasitism rate by parasitoid wasps on seed beetles among plant treatments. Our results show that damage at the seedling stage triggers compensatory responses which implies that tolerance to herbivory is enhanced or primed by early damage. Herbivory often occurs at several time points throughout plant development and this study illustrates that, for a full understanding of the factors associated with plant induced responses in a dynamic biotic environment, it is important to determine the multitrophic consequences of damage at more than one ontogenetical stage.